Effective tunneling processes in an interferometer of helical edge states with an antidot - Rizzo, Bruno (2014)
We consider an interferometer of edge states of a two-dimensional topological insulator with an antidot. We analyze the mechanisms leading to an effective tunneling with spin flip between different helical states.